Antinociceptive effectiveness of the inhibition of NCX reverse-mode action in rodent neuropathic pain model. (August 2019) - Huang, Yang; Wen, Li-Li; Xie, Jing-Dun; Ouyang, Han-Dong; Chen, Dong-Tai; Zeng, Wei-An
Background: Chronic neuropathic pain is a debilitating condition that remains difficult to treat. The Na + -Ca 2+ exchanger (NCX) is a transporter that can exchange Ca 2+ with Na + in either direction to maintain intracellular Ca 2+ homeostasis. However, the effect of NCX on neuropathic pain remains unclear. Therefore, in this study, we aimed to clarify whether neuropathic pain is altered by NCX. Methods: Adult Sprague–Dawley rats and mice (NCX2 knockout and wild type) were randomized to receive spinal nerve ligation surgery or intrathecal injection. Using behavioral testing to analyze the withdrawal thresholds and thermal withdrawal latency of rats after surgery or intrathecal injection. Immunohistochemistry and Western blotting were used to analyze the changes of NCX protein and downstream signaling pathways in rats dorsal root ganglion. We isolated the dorsal root ganglion neurons of adult rats using Fluo-4AM to detect the Ca 2+ imaging in neurons after drug treatment. Results: NCX was expressed in the sensory neurons of rodent dorsal root ganglia. NCX expression was altered in ipsilateral L4–6 dorsal root ganglion neurons in spinal nerve ligation rats. Intrathecal injection of an inhibitor of reverse-mode NCX activity (KB-R7943 5∼20 µg) had an antinociceptive effect in spinal nerve ligation rats, and the effect lasted for 3 h. We measured the expression of signaling pathway molecules in dorsal root ganglion neurons, and only the p-extracellular signal-regulated kinase (ERK) 1/2 level was reduced after intrathecal injection in the spinal nerve ligation group compared to the control group. In cultured dorsal root ganglion neurons, inhibitors of reverse-mode NCX activity (KB-R7943 and ORM-10103) restrained Ca 2+ overload after tumor necrosis factor alpha (TNF-α) or lipopolysaccharide (LPS) treatment. NCX2 knockout mice presented an antinociceptive effect that lasted for more than 28 days after spinal nerve ligation surgery. The p-ERK1/2 level in NCX2 knockout mice ipsilateral L4–6 dorsal root ganglion neurons was lower than that in wild-type mice. Conclusions: NCX proteins may mediate neuropathic pain progression via the Ca 2+ and ERK pathways. NCX represents a potential target for the treatment of neuropathic pain.